Adaptasi Mahasiswa Asal Karangasem Dalam Memilih Hunian Di Kota Denpasar (Studi Kasus Mahasiswa Rantaun Asal Karangasem) - Arya Sugiawan, I Made; Ginting Suka, Industri; D.P., Bambang (Humanis; Vol 17 No 3 (2016), 2016)
For students or new students who are being migrated to another city to pursue science, would definitely look for a place to stay for shelter. Place of residence or dwelling kos is the first thing that is needed and wanted before they continue their studies. With the residence, the students will have a new environment with a different atmosphere from their place of origin. In order to facilitate the process of adaptation of students from Karangasem, predominantly residential boarding students chose the same with students from other Karangasem. But on the other hand, it also requires the students to adapt and adjust your lifestyle to be able to socialize with fellow boarders from other region